Analisis Neraca Air (Water Balance) Pada Daerah Aliran Sungai (DAS) Rejoso Kabupaten Pasuruan - Wintyaswan, Gevan Rangga; Sumiadi, Sumiadi; Soetopo, Widandi (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2023)
One of the watershed areas in Indonesia has been identified as experiencing water balance problems in the Rejoso watershed, Pasuruan Regency, East Java, by looking at the condition of the water balance before and after the Umbulan Regional SPAM raw water was taken. Therefore, it is necessary to take measures for water management and conservation in a measurable, systematic way so that the potential negative impacts can be reduced and controlled. In this study, 2 water balance scenario simulations were also carried out to see whether the availability of water experienced a surplus or deficit using the method FJ Mock uses the Basic Month and Basic Year statistical tests. The discharge reliability level is calculated based on the Distribution Conformity Test examination of 80% with a 20% chance of failure. Calculation of the total Availability of Discharge for Domestic Water Needs, Irrigation, Fisheries, Industry and River Maintenance is 108,562 million m3/year. The Projection of Total Water Demand for Scenario 1 by taking the Umbulan Spring Debit of 4000 lt/sec for Regional SPAM is 116.757 million/m3. Projected Total Water Demand for Scenario 2 (without Industrial Groundwater) by taking Umbulan Spring Debit 5000 lt/sec for Regional SPAM is 67.780 million/m3.Dengan membandingkan keseimbangan air sebelum dan sesudah asupan air baku SPAM Regional Umbulan, ditentukan bahwa salah satu daerah aliran sungai Indonesia, DAS Rejoso di Kabupaten Pasuruan, Jawa Timur, mengalami masalah dengan keseimbangan air. Oleh karenanya perlu dilakukan langkah-langkah pengelolaan serta konservasi air secara terukur, sistematis agar potensi dampak negatif dapat dikurangi dan dikendalikan. Pada penelitian ini juga dilakukan simulasi skenario neraca air sebanyak 2 kalipercobaan untuk melihat ketersediaan air apakah mengalami Surplus atau Defisit dengan Metode FJ. Mock menggunakan uji statistika Basic Month dan Basic Year. Tingkat keandalan debit dihitung berdasarkan pemeriksaan Uji KesesuaianDistribusi sebesar 80% dengan peluang kegagalan 20%. Perhitungan total Ketersediaan Debit untuk Kebutuhan Air Domestik, Irigasi, Perikanan, Industri dan Pemeliharaan Sungai sebesar 108,562 Juta m3/Tahun. Proyeksi Kebutuhan Air Total untuk Skenario 1 dengan pengambilan Debit Mata Air Umbulan 4000 lt/dt untuk SPAM Regional adalah 116,757 Juta/m3. Proyeksi Kebutuhan Air Total untuk Skenario 2 (tanpa Air Tanah Industri) dengan pengambilan DebitMata Air Umbulan 5000 lt/dt untuk SPAM Regional adalah 67,780 Juta/m3.